Learning for jobs : OECD reviews of vocational education and training ; options for China - Kuczera, Malgorzata [Verfasser]; Field, Simon [Verfasser] (My University, 2010)
"'Learning for jobs' is an OECD study of vocational education and training (VET) designed to help countries make their VET systems more responsive to labour market needs. This special report looks at the system in China. China's education system has made dramatic advances: almost all children in China now complete lower secondary education. Around three quarters continue into upper secondary schools, with fast increasing numbers in tertiary education. At upper secondary level about half the cohort enter vocational schools - more than 20 million students. At the same time the system faces significant challenges. The government is seeking to make the system accessible to all students - by removing the fees barrier, ensuring minimum quality standards in all vocational schools, and in providing adequate high quality workplace training opportunities. The OECD review assesses the main challenges faced by the VET system and presents an interconnected package of policy recommendations. For each recommendation, the report describes the challenge, the recommendation itself, supporting arguments, and issues of implementation." (Hrsg., BIBB-Doku)
Keywords: S System beruflicher Bildung; S 4.1 Finanzierungsquellen; L 6.2 Qualitätsmanagement/Qualitätssicherung; I 2.3.4 Asien; Berufsbildungssystem; Berufsbildungspolitik; Berufsbildendes Schulwesen; Betriebliche Berufsausbildung; Bildungsfinanzierung; Qualitätssicherung; Quantitative Angaben; China